Review Article: Potensi Bahan Alam Produk Lokal Indonesia sebagai Bahan Aktif Skincare - Shafa Ulya Rahmah; Shafa Alifia Nurjihan; Nani Kartinah; Mizan Humaidy (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract [Review Article: The Potential of Indonesian Botanicals as Active Ingredients in Skincare] Indonesia possesses a rich diversity and abundance of bioactive compounds with significant pharmacological potential. The increasing consumer demand for safe, effective, and environmentally friendly cosmetic products has spurred rapid development in the use of natural ingredients as active components in the local skincare industry. This study aims to explore the potential of abundant natural ingredients in Indonesia, such as Centella asiatica, Melaleuca alternifolia, Aloe vera, Artemisia vulgaris, and Psoralea corylifolia, as active components in skincare products, focusing on innovations and the challenges faced by the industry. A systematic review was conducted using the Systematic Mapping Study (SMS) method. A search for relevant articles published between 2015 and 2025 was performed on the Google Scholar, PubMed, and ScienceDirect databases through a two-stage process: screening of titles and abstracts, followed by a full-text evaluation of the journals. The research output includes a classification, an overview of trends (innovations), and the identification of gaps or problems (formulation constraints). The results indicate that these five natural ingredients are consistently reported to possess antioxidant, anti-inflammatory, antimicrobial, and anti-aging activities. The most prominent innovation trends include the use of synergistic combinations of active ingredients, microneedle delivery systems, and nanoparticle encapsulation to achieve maximum efficacy. The primary challenges predominantly identified are issues with compound stability, low bioavailability, and variability in raw material quality. This review provides a research map that highlights the gap between bioactive potential and formulation challenges, offering direction for future research and the development of globally competitive local skincare products. Keywords: natural ingredients, skincare, local cosmetics, article review